Modelling the Mechanism of Mineral-Binders’ Hydration Processes in a Macro–Micro–Nanosystem - Derevianko, Victor; Дерев’янко, Віктор Миколайович; Kondratieva, Natalia; Кондратьєва, Наталія Вікторівна; Hryshko, Hanna; Гришко, Ганна Миколаївна; Sanytskyi, Myroslav; Синицький, Мирослав Андрійович (Інститут металофізики ім. Г. В. Курдюмова НАН України, 2020)
Today, the topical issue is the development of a model of mineral binders’ hy-dration processes that would allow taking into account the most initial parame-ters and characteristics, conditions, and the mechanism of the hydration pro-cess. Developing this model requires a large amount of information. Most mod-els only allow for the effect of original components. Besides, with the acquired properties, the optimization process becomes complicated due to the increase in a number of models in connection with the application of optimality criteria for the relative properties. Moreover, due to the fact that there is no specified ratio of components topochemically hydrated in the gypsum system under a solu-tion-based scheme, the hydration process becomes more complicated. Thus, to develop the model, we should justify a large number of assumptions. Besides, selecting the optimality criteria by indirect indicators does not give a clear pic-ture of the intended end use of the model. We should also take into account a scaling level and a relationship between the macro-, micro-, and nanoscales. Modelling of mineral binders’ hydration processes is presented in the form of a system that changes over time and undergoes macro- to microscale, micro- to nanoscale, nano- to microscale, and micro- to macroscale stages, using a direct model as an example. The transition from a macrosystem and a microsystem to a nanosystem with the formation of a dispersion medium is presented in the form of a surface consisting of nanoparticles in the multidimensional phase space. The surface is the interface between the structural elements and the dis persion medium. The second surface is the interface between the dispersion medium and the hardened structure. At the interface, a partial transition from macro- and microsystems to a nanosystem occurs as well as a topochemical re-action of calcium-sulphate transition from hemihydrate to dihydrate. The most high-strength skeleton frame can be developed by adjusting the values of solid surface and crystallization nuclei, which affect the initial three-dimensional structure and the formation of a durable framework. The internal stresses leading to softening of a structure that has not been yet formed do not arise because the blocks’ splicing occurs in a free space. Chemical potential is a unit to measure a change in a characteristic function at constant parameters and mass fractions (concentrations) of all substances except the mass fraction (concentration) of a component, the amount of which varies in the system. If the hydration process is topochemical, structure formation rate will be de-pendent on particle-size distribution and intraparticle diffusion rate. На сьогоднішній день актуальним є розробка моделі процесів гідратації мінеральних в’яжучих, яка б дозволяла врахувати найбільш вихідні параметри та характеристики, умови та механізм процесу гідратації. Розробка цієї моделі потребує великої кількості інформації. Більшість моделей дозволяють використовувати лише оригінальні компоненти. Крім того, з набутими властивостями процес оптимізації ускладнюється через збільшення кількості моделей у зв'язку із застосуванням критеріїв оптимальності відносних властивостей. Крім того, у зв’язку з відсутністю заданого співвідношення компонентів, топохімічно гідратованих у гіпсовій системі за розчинною схемою, процес гідратації ускладнюється. Таким чином, для розробки моделі необхідно обґрунтувати велику кількість припущень. Крім того, вибір критеріїв оптимальності за непрямими показниками не дає чіткої картини передбачуваного кінцевого використання моделі. Ми також повинні взяти до уваги рівень масштабування та співвідношення між макро-, мікро- та наномасштабами. На прикладі прямої моделі моделювання процесів гідратації мінеральних в’яжучих представлено у вигляді системи, яка змінюється з часом і проходить стадії від макро- до мікромасштабу, мікро- до наномасштабу, нано- до мікромасштабу та мікро- до макромасштабу. Перехід від макро- та мікросистеми до наносистеми з утворенням дисперсійного середовища представлено у вигляді поверхні, що складається з наночастинок у багатовимірному фазовому просторі. Поверхня є межею розділу між елементами конструкції та дисперсійним середовищем. Друга поверхня є межею розділу між дисперсійним середовищем і зміцненою структурою. На межі розділу відбувається частковий перехід від макро- і мікросистеми до наносистеми, а також топохімічна реакція кальцій-сульфатного переходу від напівгідрату до дигідрату. Найбільш високоміцний скелетний каркас можна розробити шляхом регулювання значень твердої поверхні та зародків кристалізації, які впливають на початкову тривимірну структуру та формування міцного каркасу. Внутрішні напруги, що призводять до розм’якшення ще не сформованої конструкції, не виникають, оскільки зрощення блоків відбувається у вільному просторі. Хімічний потенціал - одиниця вимірювання зміни характеристичної функції при постійних параметрах і масових частках (концентраціях) усіх речовин, крім масової частки (концентрації) компонента, кількість якого в системі змінюється. Якщо процес гідратації є топохімічним, швидкість формування структури буде залежати від розподілу частинок за розміром і швидкості дифузії всередині частинок.
Моделювання механізму процесів гідратації мінералів-зв’язуючих речовин у макро–мікро -наносистемі
Keywords: hydration; гідратація; mineral binders; мінеральні в'яжучі; nanosystem; наносистема; hardened structure; зміцнена структура; modelling; моделювання